THE PROSPECTS OF HALAL TOURISM IN BANYUWANGI: A CASE STUDY ON NATURAL AND LOCAL CULTURAL POTENTIALS - Kanom, Putu Ngurah Rusmawan (Al-Makrifat: jurnal kajian Islam, 2025)
This study explores the prospects of halal tourism in Banyuwangi, focusing on the integration of natural and cultural potentials as the foundation for developing Sharia compliant tourism destinations. The core issue addressed in this research is the suboptimal utilization of local values to support a sustainable halal tourism ecosystem, despite Banyuwangi’s abundant natural and cultural resources. The aim of this study is to identify and analyze the development opportunities for halal tourism in Banyuwangi through local wisdom. This qualitative research employs a case study approach, involving in-depth interviews with academics, tourism industry stakeholders, and tourists, alongside field observations and documentation. Data were analyzed using the Miles and Huberman model with validity ensured through credibility, transferability, dependability, and confirmability. Findings indicate that although Banyuwangi is not yet formally designated as a halal tourism destination, halal tourism practices have organically developed through the religious values of the Osing community and their environmental preservation efforts. These findings highlight the importance of culturally rooted approaches in developing halal tourism models, offering a framework that can be adapted by other regions with similar socio-cultural and ecological characteristics.